Digging Up the Roots: Taxonomic and Phylogenetic Disentanglements in Corticiaceae s.s. (Corticiales, Basidiomycota) and Evolution of Nutritional Modes - Ghobad-Nejhad, Masoomeh; Langer, Ewald; Nakasone, Karen; Diederich, Paul; Nilsson, R. Henrik; Rajchenberg, Mario; Ginns, James (Frontiers in Microbiology, 2021)
Corticiaceae is one of the traditional families of the Agaricomycetes and served for a long time as a convenient placement for basidiomycetes with a resupinate, corticioid form of fruiting body. Molecular studies have helped to assign many corticioid fungi to diverse families and orders; however, Corticiaceae still lacks a phylogenetic characterization and modern circumscription. Here, we provide the first comprehensive phylogenetic and taxonomic revision of the family Corticiaceae based on extensive type studies and sequences of nLSU, ITS, IGS, nSSU, and mtSSU regions. Our analyses support the recognition of ten monophyletic genera in the Corticiaceae, and show that nutritional mode is not a robust basis for generic delimitations in the family. The genus Bernardia and the species Corticium thailandicum, Erythricium vernum, and Marchandiomyces allantosporus are described as new to science, and five new combinations are proposed. Moreover, ancestral character state reconstruction revealed that saprotrophy is the plesiomorphic nutritional mode in the Corticiaceae, while several transitions have occurred to diverse nutritional modes in this family. Identification keys are provided to the genera in Corticiaceae s.s. as well as to the species in Corticium, Erythricium, Laetisaria, and Marchandiomyces.